2000
DOI: 10.1037/1076-898x.6.3.236
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sleep deprivation on decision making: A review.

Abstract: Few sleep deprivation (SD) studies involve realism or high-level decision making, factors relevant to managers, military commanders, and so forth, who are undergoing prolonged work during crises. Instead, research has favored simple tasks sensitive to SD mostly because of their dull monotony. In contrast, complex rule-based, convergent, and logical tasks are unaffected by short-term SD, seemingly because of heightened participant interest and compensatory effort. However, recent findings show that despite this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
686
4
15

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 931 publications
(732 citation statements)
references
References 93 publications
27
686
4
15
Order By: Relevance
“…Thus, acute sleep deprivation that temporarily affects attention could, consequently, also alter the phenomena that constitute the neurobiological bases of CAP. From a neuropsychological perspective— which predicts that all memory-based tasks should be affected by SD [13]—studies have shown that language tasks that require sustained attention and higher level processing, such as reading comprehension, were negatively affected by sleep deprivation, whereas other tasks that rely on basic language processing, such as order recall or category recall, were not affected [26]. Furthermore, some executive functions, the ability to execute complex tasks (i.e., creative problem solving), decision making, attention, and vigilance have been shown to be impaired by sleep loss [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, acute sleep deprivation that temporarily affects attention could, consequently, also alter the phenomena that constitute the neurobiological bases of CAP. From a neuropsychological perspective— which predicts that all memory-based tasks should be affected by SD [13]—studies have shown that language tasks that require sustained attention and higher level processing, such as reading comprehension, were negatively affected by sleep deprivation, whereas other tasks that rely on basic language processing, such as order recall or category recall, were not affected [26]. Furthermore, some executive functions, the ability to execute complex tasks (i.e., creative problem solving), decision making, attention, and vigilance have been shown to be impaired by sleep loss [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation impacts several functions associated with prefrontal cortex (PFC) activity [13,14] and auditory temporal resolution is a perceptual function associated with PFC activity [15]. Thus, it is reasonable to posit that sleep deprivation may impair CAP through circuits involving the PFC.…”
Section: Introductionmentioning
confidence: 99%
“…2 To begin with, isolation heightens the stress of custodial interrogation, especially after extended periods of time, thus increasing a suspect's motive to escape. Controlled laboratory experiments show that fatigue and sleep deprivation, which accompany prolonged periods of isolation, can heighten susceptibility to influence and impair complex decision-making abilities (Blagrove, 1996;Harrison & Horne, 2000). Thus, it comes as little surprise that whereas most police interrogations last for less than 2 hours (Leo, 1996a), and whereas 3 or 4 hours are usually sufficient (Inbau et al, 2001), a recent analysis of proven false confession cases in which interrogation times were available revealed that 34% lasted 6 -12 hours, 39% lasted 12-24 hours, and the mean was 16.3 hours (Drizin & Leo, 2004).…”
Section: The Interrogationmentioning
confidence: 99%
“…TSD effects on frontal lobe functions often include reductions in response inhibition (Harrison and Horne, 1997), complex decision-making (Harrison and Horne, 2000), divergent thinking (Wimmer et al, 1992), word generation and appropriate intonation (Drummond et al, 2001), a delayed-match-to-sample task , and verbal working memory (Mu et al, 2005;Chee and Choo, 2004;Choo et al, 2005). According to Durmer and Dinges (2005), the neurocognitive abilities that are particularly vulnerable to sleep deprivation include executive attention, working memory, and divergent higher cognitive functions.…”
Section: Introductionmentioning
confidence: 99%